Pengaruh EPS, ROE, dan ROA terhadap Harga Saham Perusahaan Consumer Goods Periode 2015-2020 - Rizal Rosikin; Maulida Nurhidayati (Institut Agama Islam Negeri Ponorogo, 2023)
Prospective investors must do a financial ratio analysis to determine the best and most profitable investment decisions. In theory, the value of Earning Per Share (EPS), Return on Equity (ROE), and Return On Assets (ROA) increases and will increase stock prices. The identification results show that when the EPS, ROE, and ROA of consumer goods companies have increased EPS, ROE, ROA, and Stock Price, the stock prices of consumer goods companies have decreased. This shows that there needs to be more theory and data. Based on this, this study aims to examine and analyze the effect of EPS, ROE, and ROA on the stock price of Consumer Goods companies partially or simultaneously. This type of research is quantitative research using secondary data. There is also data collection using a documentation study. The data used in this study is in the form of annual reports of Consumer Goods companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2020 period. The analytical method used is panel data regression analysis with the stages of panel data regression model estimation, panel data regression model selection, classical assumption test, and significance test; the software used is Eviews 9.0. The results of this study indicate that the EPS variable partially has a positive effect on stock prices. ROE variable partially does not affect stock prices. The ROA variable partially has a negative effect on the Stock Price. The EPS, ROE, and ROA variables simultaneously significantly affect the Stock Price. Adjusted R-squared has a value of 77.135%. This shows that EPS, ROE, and ROA in this study affect 77.135% of stock prices, while other variables outside this study influence 22.86%.